Ubiquitin and transcription: The SCF(Met30)/Met4 pathway, a (protein-) complex issue - Ouni, Ikram (Landes Bioscience, 2011)
Ubiquitylation has emerged as an omnipresent factor at all levels of transcriptional regulation. A recent study that describes the yeast transcriptional activator Met4 as a functional component of the very same ubiquitin ligase that regulates its own activity highlights the close relation between transcription and the ubiquitin proteasome system.